(untitled) (Medico Legal Update, 2020)
The value of scientific research depends on the type of data and the accuracy and quality of the devices used in these devices and foot scanner (foot scan), a device for the analysis of walking movements and helps in the detection of the values of many variables of the amount of pressure and the deviation and deviation of the foot and direction and time of contact and the extent of benefit Of these variables in the identification of errors and the development of appropriate exercises appropriate to them and this is what the importance of research as a serious attempt to identify the current mechanical situation of this category of disabled and study the details of this case and the problem of research is the lack of appropriate corrective exercises and the objective of the research to design corrective exercises and knowledge of their effect on some values of the biomechanical variables of the footprint at a speed of (2 km / h). Corrective exercises Led to an improvement in the level of walking of the sample by the development of the values of the variables investigated.